2013
DOI: 10.1002/bies.201300052
|View full text |Cite
|
Sign up to set email alerts
|

Cell death proteins: An evolutionary role in cellular adaptation before the advent of apoptosis

Abstract: Programmed cell death (PCD) or apoptosis is a broadly conserved phenomenon in metazoans, whereby activation of canonical signal pathways induces an ordered dismantling and death of a cell. Paradoxically, the constituent proteins and pathways of PCD (most notably the metacaspase/caspase protease mediated signal pathways) have been demonstrated to retain non-death functions across all phyla including yeast, nematodes, drosophila, and mammals. The ancient conservation of both death and non-death functions of PCD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 91 publications
2
21
0
Order By: Relevance
“…4 B and C) suggest that CK2 ensures protein stability of Pax7 in proliferating/self-renewing SCs and loss of this kinase function is a key step in initiating myogenic differentiation. Caspase 3 activation is an essential cue for promoting differentiation of committed progenitor cells (12). Our study demonstrates that caspase 3 also acts at a much earlier step in the life cycle of muscle stem cells, by limiting the self-renewal process.…”
Section: Phosphorylation Of Pax7 Via Ck2 Prevents Caspase 3 Cleavage Andmentioning
confidence: 84%
See 3 more Smart Citations
“…4 B and C) suggest that CK2 ensures protein stability of Pax7 in proliferating/self-renewing SCs and loss of this kinase function is a key step in initiating myogenic differentiation. Caspase 3 activation is an essential cue for promoting differentiation of committed progenitor cells (12). Our study demonstrates that caspase 3 also acts at a much earlier step in the life cycle of muscle stem cells, by limiting the self-renewal process.…”
Section: Phosphorylation Of Pax7 Via Ck2 Prevents Caspase 3 Cleavage Andmentioning
confidence: 84%
“…1A). This temporal activity pattern is reminiscent of caspase 3 activation in other nondeath settings, which include differentiation of committed skeletal myoblasts and stem cells from a variety of lineages, including neuronal and hematopoietic progenitors (12,13,16,17).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 This apparent paradox is best exemplified in the study of cell differentiation, where caspase activity has been shown to modify the differentiation of virtually all somatic cell types tested, across a diverse spectrum of metazoan organisms. 4, 5 …”
Section: Open Questionsmentioning
confidence: 99%